Unraveling the molecular basis of snake venom nerve growth factor: human TrkA recognition through molecular dynamics simulation and comparison with human nerve growth factor - Devi, Shrudhi; Jayaraman, Gurunathan (Frontiers in Bioinformatics, 2025)
IntroductionNeurodegenerative diseases pose significant challenges owing to the limited number of effective therapies. Nerve growth factor (NGF) plays a crucial role in neuronal survival and differentiation through tropomyosin receptor kinase A (TrkA). Although snake venom NGF (sNGF) has been studied for its ability to activate TrkA, the binding modes and associated dynamics remain unclear compared to those of human NGF (hNGF). Herein, we explored the possibilities of NGFs from Daboia russelii and Naja naja as potential therapeutic alternatives to hNGF by comparing the structural similarities and conserved binding residues.MethodsThe active sites were identified through a literature review, molecular docking was performed using HADDOCK, and molecular dynamics simulation was performed to analyse the stabilities of the complexes; then, PRODIGY and molecular mechanics Poisson–Boltzmann surface area were used to determine the binding affinities.ResultsThe different sNGFs exhibited stronger binding affinities and stabilities than hNGF, while principal component analysis and the free energy landscape indicated constrained conformational flexibilities suggestive of an adaptive mechanism in sNGF for effective receptor engagement. A network coevolutionary analysis was performed, which showed the pattern in which the amino acids were coevolved and conserved throughout the simulations.DiscussionThese findings indicate that NGFs from D. russelii and N. naja are promising therapeutic candidates for treating neurodegenerative disorders and warrant further in vivo validation.